2015
DOI: 10.1161/circresaha.117.305962
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a Plays a Key Role in Cardiac Repair and Regeneration Following Myocardial Infarction

Abstract: Rationale In response to injury, the rodent heart is capable of virtually full regeneration via cardiomyocyte proliferation very early in life. This regenerative capacity, however, is diminished as early as one week post-natal and remains lost in adulthood. The mechanisms that dictate post injury cardiomyocyte proliferation early in life remain unclear. Objective To delineate the role of miR-34a, a regulator of age-associated physiology, in regulating cardiac regeneration secondary to myocardial infarction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
149
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 44 publications
6
149
0
3
Order By: Relevance
“…An elevation in miR-34a expression has also been linked to reduced sirtuin1 expression in obesity and arteries from aged human and mice (Li et al, 2011;Choi et al, 2013;Fu et al, 2014) and accelerated apoptosis of cardiomyocytes in neonatal and adult mouse hearts (Yang et al, 2015). In conclusion, and as summarized in Fig.…”
Section: Discussionmentioning
confidence: 58%
“…An elevation in miR-34a expression has also been linked to reduced sirtuin1 expression in obesity and arteries from aged human and mice (Li et al, 2011;Choi et al, 2013;Fu et al, 2014) and accelerated apoptosis of cardiomyocytes in neonatal and adult mouse hearts (Yang et al, 2015). In conclusion, and as summarized in Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, a number of studies recently indicated the downregulation of the expression of miR-449 in various human malignancies, including lung cancer, prostate cancer, and adrenal hyperplasia [28, 29]. miR-34 has been reported to function in cardiovascular disorders by regulating apoptosis, telomere attrition, DNA damage, and inflammatory response [30-33]. However, no study has reported the involvement of miR-449 in the cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these miRNAs, or their family members, have previously been shown to be elevated in hearts of cardiac stress mouse models associated with fibrosis (e.g., MI, pressure overload, dilated cardiomyopathy and atrial fibrillation), and targeting these miRNAs was effective in preventing or attenuating fibrosis in vivo (5,(7)(8)(9)(10)(11)(12)(13)(14). Other studies have identified numerous additional miRNAs dysregulated in cardiac fibrotic models.…”
Section: Other Mirnas Implicated In Regulating Cardiac Fibrosismentioning
confidence: 99%